Pharmacokinetic analysis and tissue distribution of Vam3 in the rat by a validated LC-MS/MS method - Zhang, Ruixia (Acta Pharm Sin B, 2015)
Vam3 is a potential pharmacologically active ingredient isolated from Vitis amurensis Rupr. A rapid, simple and sensitive method to determine Vam3 levels in rat plasma and tissue was developed based on LC-MS/MS. Vam3 and an internal standard (IS) were chromatographed on a C18 short column with acetonitrile–0.1% formic acid in water by gradient elution. MS detection was performed by electrospray ionization in negative ion multiple reaction–monitoring modes. This method monitored the transitions m/z 451.0→345.0 and m/z 301.0→164.0 for Vam3 and IS, respectively. The calibration curve was linear over a concentration range of 1.64–1000 ng/mL. The inter-day and intra-day variabilities in precision was less than 12.8%, while the inter-day and intra-day accuracies ranged from –10.60% to 9.08% in plasma and tissue homogenates. This method was applied to investigate the pharmacokinetics and tissue distribution of Vam3 in rats. The results indicated that Vam3 had poor absorption into systemic circulation and extensive tissue distribution after oral administration, and the absolute bioavailability was low (0.79%). Vam3 had a relatively long terminal elimination half-life in lung, and the highest concentration was found in small intestinal tissue. The developed method and the pharmacokinetic data can provide a basis for further studies on the bioactivity of Vam3.